[Workers packing granulated sugar] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Packing 2 kilogram bags of granulated sugar for domestic use by workers of the Caroni Ltd., Ste Madelene Refinery.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar -- Packing -- Trinidad and Tobago; Caroni (1975) Limited